Analisis Dampak Guncangan Eksternal World Oil Price dan Federal Fund Rate terhadap Variabel Makroekonomi Indonesia - Sukma, Nefi; Andrianus, Fery; Kamarni, Neng (SAFE-Network, 2025)
This study aims to analyze the impact of external shocks, namely world oil prices and global interest rates,on Indonesia’s macroeconomic variables, such as domestic output, inflation, and the real effective exchange rate. Additionally, it examines the effectiveness of Bank Indonesia’s monetary policy through the implementation of the domestic interest rate using the Structural Vector Autoregression method. The data used are monthly secondary time-series data, comprising external shock variables world oil prices and global interest rates and domestic variables output, price levels, interest rates, money supply, and real effective exchange rate spanning from January 2008 to December 2022. This research is motivated by the impact of WOP and FFR shocks during the global financial crisis and the Covid-19 pandemic. The Impulse Response Function results indicate that domestic output, price levels, and the real effective exchange rate respond negatively to WOP shocks and FFR reductions. Furthermore, domestic output and the real effective exchange rate exhibit a negative response to the domestic interest rate, while the price level generally responds positively. The Forecast Error Variance Decomposition results show that, in addition to the significant contributions of world oil price and global interest rate shocks, the variables output, price levels, interest rates, money supply, and real effective exchange rate also have substantial contributions to themselves and to changes in other macroeconomic variables.